2012
DOI: 10.1038/nm.2871
|View full text |Cite
|
Sign up to set email alerts
|

Bat3 promotes T cell responses and autoimmunity by repressing Tim-3–mediated cell death and exhaustion

Abstract: T cell immunoglobulin and mucin domain-containing-3 (Tim-3) is an inhibitory receptor expressed on exhausted T cells during HIV-1 and HCV infection. By contrast, Tim-3 expression and function are defective in multiple human autoimmune diseases. However, the molecular mechanisms governing Tim-3 function remain poorly understood. Here we show that HLA-B-associated transcript 3 (Bat3) binds to, and represses the function of Tim-3. Bat3-deficient T cells display elevated expression of exhaustion markers, and knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
297
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(326 citation statements)
references
References 51 publications
13
297
0
1
Order By: Relevance
“…Investigators from a recent study reported that human leukocyte antigen B-associated transcript 3 (Bat3) binds to the cytoplasmic tail of Tim-3. Galectin-9-induced phosphorylation of the Tim-3 cytoplasmic tail triggers the release of Bat3, resulting in the accumulation of the catalytically inactive form of the lymphocyte-specific protein tyrosine kinase (Lck) and defective IL-2 and IFN-g production (25). These data suggest that Bat3 acts as a negative regulator of the inhibitory function of Tim-3.…”
Section: Distinguishing Features Of Tim-3mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators from a recent study reported that human leukocyte antigen B-associated transcript 3 (Bat3) binds to the cytoplasmic tail of Tim-3. Galectin-9-induced phosphorylation of the Tim-3 cytoplasmic tail triggers the release of Bat3, resulting in the accumulation of the catalytically inactive form of the lymphocyte-specific protein tyrosine kinase (Lck) and defective IL-2 and IFN-g production (25). These data suggest that Bat3 acts as a negative regulator of the inhibitory function of Tim-3.…”
Section: Distinguishing Features Of Tim-3mentioning
confidence: 99%
“…1A and B). Indeed, Tim-3/PD-1 pathway coblockade is more effective than either Tim-3 or PD-1 pathway blockade alone at restoring tumor antigen-specific IFN-g production in CD8 þ T cells from tumor-bearing mice (25). Moreover, Tim-3/PD-1 pathway coblockade also drives the downmodulation of several genes associated with potent Tregsuppressor function in Tim-3 þ Tregs (21).…”
Section: Targeting Tim-3 For Cancer Immunotherapymentioning
confidence: 99%
“…62 Recent studies implicated the human leukocyte antigen B-associated transcript (Bat3) as a molecular adaptor linked to the intracellular tail of TIM-3, which protects Th1 cells from galectin-9-induced apoptosis. 63 However, studies on TIM-3-galectin-9 interactions were so far based on exposure to exogenous galectin-9. Whether an additional ligand competes with galectin-9 for TIM-3 is less clear.…”
Section: Galectin Counter-receptors In the Initiation Of Cell Deathmentioning
confidence: 99%
“…The genomic localization suggested a role in immune response, and this suggestion has been supported by evidence of its roles in Th1 cell survival (9), natural killer cell cytotoxicity (10), and MHC class II molecule presentation (11,12). The initial Bag6 link to apoptosis was based on its interaction with Reaper, an apoptosis-inducing Drosophila protein (13).…”
mentioning
confidence: 95%